The impact of natural disasters on banks' impairment flow: Evidence from Germany - Iliriana Shala; Benno Schumacher (Deutsche Bundesbank, 2022)
Climate change causes natural disasters to occur at higher frequency and increased severity. Using a unique dataset on German banks, this paper explores how regionally less diversified banks in Germany adjusted their loan loss provisioning following the severe summer flood of 2013, which affected widespread regions mostly in Eastern Germany. The analysis uses a difference-in-differences estimation with banks being allocated to the treatment and control group based on the region of their primary operational activities. This paper yields various results: German savings and cooperative banks located in the affected regions experienced a significantly higher, but ephemeral, impairment flow in the years following the flood. Impairments were mostly driven by corporate loans concentrated in specific sectors, such as agriculture and manufacturing, and to some extent by retail mortgage loans. While results suggest that the profitability of banks is impacted by additional factors, we do not find evidence that banks suffered from damages to their own property. The results are robust to various model specifications.
Keywords: C12; C21; C23; G21; Q54; 330; Natural disaster; climate change; credit risk; profitability; difference-in-differences